An improved requirement change management model for agile software development - Saher, Najia (2021)
Business requirements for software development projects are volatile and continuously need improvement. Hence, popularity of Agile methodology increases as it welcomes requirement changes during the Agile Software Development (ASD). However, existing models merely focus on change of functional requirements that are not adequate to achieve software sustainability and support change requirement processes. Therefore, this study proposes an improved Agile Requirement Change Management (ARCM) Model which provides a better support of non-functional requirement changes in ASD for achieving software sustainability. This study was carried out in four phases. Phase one is a theoretical study that examined the important issues and practices of requirement change in ASD. Then, in phase two, an exploratory study was conducted to investigate current practices of requirement changes in ASD. The study involved 137 software practitioners from Pakistan. While in phase three, the findings from the previous phases were used to construct the ARCM model. The model was constructed by adapting Plan-Do-Check-Act (PDCA) method which consists of four 4 stages. Every stage provides well-defined aims, processes, activities, and practices. Finally, the model was evaluated by using expert review and case study approaches. There were six experts involved to verify the model and two case studies which involved two software companies from Pakistan were carried out to validate the applicability of the proposed model. The study proposes the ARCM model that consists of three main components: sustainability characteristics for handling non-functional requirements, sustainability analysis method for performing impact and risk analysis and assessment mechanism of ARCM using Goal Question Metrics (GQM) method. The evaluation result shown that the ARCM Model gained software practitioners’ satisfaction and able to be executed in a real environment. From the theoretical perspective, this study introduces the ARCM Model that contributed to the field of Agile Requirement Management, as well as the empirical findings that focused on the current issues, challenges and practices of RCM. Moreover, the ARCM model provides a solution for handling the nonfunctional requirements changes in ASD. Consequently, these findings are beneficial to Agile software practitioners and researchers to ensure the software sustainability are fulfilled hence empowers the companies to improve their value delivery.